ANALISIS MAKNA DENOTATIF DAN KONOTATIF TERHADAP CITRA VISUAL KOMIK 101% ♥ INDONESIA - Ni Luh Pangestu Widya Sari; Ni Nyoman Sri Witari; Mursal - (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2013)
Nowadays, comic has important roles in which one of them is as media in balancing phenomena of cultures battle. Its characteristics, which are global, unique, and attractive by connecting pictures with verbal text, are able to attract people’s attention. The 101% ♥ Indonesia comic is one example of participations of a comic author in educating the readers by presenting nasionalism themes. This article reviews the 101% ♥ Indonesia comic which was launched in 2012 by a comic author Vbi Djenggotten. By using descriptive analysis research method, it is aiming at describing and explaining the denotative and connotative of the 101% ♥ Indonesia comic.Keywords : the 101% ♥ Indonesia comic, denotative and connotative.